Dental Negligence During Prosthetic Treatment - Pradyumna Ku Sahoo1, Smita R. Priyadarshini2, Kajal Kiran Sahoo3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dentists treat patients intending to restore the patient’s health. However adverse effects may occur despiteall their efforts, some of which could have otherwise been prevented, hence amounting to malpractice.Any patient coming to the dental office needs to be diagnosed accurately first to formulate the correcttreatment plan. Its the sole responsibility of the clinician to make the patient aware of the treatment needsand difficulties during and post the procedures. A thorough diagnosis with a proper record of the case history& consent should be obtained. As the dental malpractice lawsuits are extremely, expensive and emotionallydraining for the clinician.